SIMULATION MODEL FOR STUDYING THE EFFICIENCY OF DENORMALIZATION OF A RELATIONAL DATABASE IN AN INFORMATION SYSTEM - Kungurtsev, A. B.; Zinovatnaya, S. L. (Radio Electronics, Computer Science, Control, 2024)
It is recommended to execute denormalization of relations scheme after the careful testing of the information system productivity. A simulation model for testing of the system conduct in the conditions of application of different denormalization variants is offered. On the basis of this model a program instrument is realized to allow to probe databases, created with the use of the different database management systems.